2015
DOI: 10.1186/s12891-015-0775-z
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of action for hyaluronic acid treatment in the osteoarthritic knee: a systematic review

Abstract: BackgroundKnee osteoarthritis (OA) is one of the leading causes of disability within the adult population. Current treatment options for OA of the knee include intra-articular (IA) hyaluronic acid (HA), a molecule found intrinsically within the knee joint that provides viscoelastic properties to the synovial fluid. A variety of mechanisms in which HA is thought to combat knee OA are reported in the current basic literature.MethodsWe conducted a comprehensive literature search to identify currently available pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
325
0
34

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(365 citation statements)
references
References 133 publications
(150 reference statements)
6
325
0
34
Order By: Relevance
“…El AH es una molécula que se encuentra intrínsecamente en la articulación de la rodilla, dándole propiedades viscoelásticas al líquido sinovial (14). A medida que la artrosis progresa, la concentración natural de AH disminuye, reduciendo las propiedades mecánicas/viscoelásticas propias del líquido sinovial (14).…”
Section: áCido Hialurónico -Hylan (áCido Hialurónico De Alto Peso Molunclassified
See 1 more Smart Citation
“…El AH es una molécula que se encuentra intrínsecamente en la articulación de la rodilla, dándole propiedades viscoelásticas al líquido sinovial (14). A medida que la artrosis progresa, la concentración natural de AH disminuye, reduciendo las propiedades mecánicas/viscoelásticas propias del líquido sinovial (14).…”
Section: áCido Hialurónico -Hylan (áCido Hialurónico De Alto Peso Molunclassified
“…A medida que la artrosis progresa, la concentración natural de AH disminuye, reduciendo las propiedades mecánicas/viscoelásticas propias del líquido sinovial (14).…”
Section: áCido Hialurónico -Hylan (áCido Hialurónico De Alto Peso Molunclassified
“…However, medical studies (Ghosh, 2002) shown positive effect of viscosupplementation even 6 months after injection whilst exogenous hyaluronic acid can be detected in synovial fluid just few weeks after injection. This points out on another effects of hyaluronic acid like synthesis of endogenous hyaluronic acid or anti-inflammatory effect (Altman, 2015). However, the dominant effect of viscosupplementation and physiological phenomenon responsible for these results was not clarified yet.…”
Section: Introductionmentioning
confidence: 99%
“…Since, with age, the body starts to decrease the production of glycosaminoglycans from glucose (7), oral intake of GlcNac may increase synthesis of cartilage glycosaminoglycans and improve the symptoms of the knee joint (8). Because glucosamine consists of glycosaminoglycan after being converted into GlcNac in the cells of the target tissue, GlcNac is considered to be more effective in small amounts than glucosamine for improving knee functions.…”
Section: Introductionmentioning
confidence: 99%